منهجية حساب الخصائص الترموديناميكية الحرورية للبلورات عند درجات الحرارة العالية - سليمان سليمان; نور الدين صلاح الدين (Latakia University Journal -Basic Sciences Series, 2018)
يعنى هذا البحث بعرض منهجية متكاملة لحساب الخصائص الترموديناميكية الحرورية للبلورات على امتداد المنحنيات الإيزوحرارية الموافقة لكل درجات الحرارة بما في ذلك المساوية لدرجة حرارة انصهار البلورة فأعلى عند قيم مختلفة لحجمها المولي تصل حتى قيمته الموافقة لمنحنيات التوازن التجريبية مع الطورين الغازي والسائل وضمن حدود تطبيق التقريب شبه التقليدي. وتقوم هذه المنهجية على أخذ قوى التأثير المتبادل الثنائية و قوى التأثير المتبادل الثلاثية بعين الحسبان. وبغية التأكد من فعالية المنهجية المقترحة طبقت على بلورة الأرغون عند درجة حرارة الانصهار تحت الضغط الجوي (83.806) درجة كلفن حيث تتوفر المعطيات التجريبية وقورنت بالنتائج التجريبية والمعطيات النظرية لباحثين آخرين. تشير المقارنة بوضوح إلى توافق النتائج المحسوبة مع النتائج التجريبية. This work proposes a methodology for calculating the calorific thermodynamic properties of crystals along isothermal curves, expanded from any temperature through melting point temperature and up at different molar volume values expanded up to its value, corresponded experimental equilibrium curves with gaseous and liquid phases within the framework of quasi-classical approximation. The pair-wise inter-atomic forces in conjunction with three-body forces were taken into consideration in methodology. In order to ascertain the effectiveness of the proposed methodology it was applied for calculating the calorific properties of crystalline Argon at 83.806K temperature where experimental data are available. The calculated results were compared with available experimental data and theoretical results of other authors. The comparison clearly indicates that the calculated results coincide well with the experimental results.